2015
DOI: 10.3390/ijgi4010220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spatial Interpolation Methods to Map the Bathymetry of an Amazonian Hydroelectric Reservoir to Aid in Decision Making for Water Management

Abstract: Abstract:The generation of reliable information for improving the understanding of hydroelectric reservoir dynamics is fundamental for guiding decision-makers to implement best management practices. In this way, we assessed the performance of different interpolation algorithms to map the bathymetry of the Tucuruí hydroelectric reservoir, located in the Brazilian Amazon, as an aid to manage and operate Amazonian reservoirs. We evaluated three different deterministic and one geostatistical algorithms. The perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 14 publications
(31 reference statements)
6
48
0
1
Order By: Relevance
“…In fact, both the IDW and OK methods performed quite similarly, thus one of the methods could be adopted in this study. Our result was also similar in comparison to other studies found in the literature: (i) Curtarelli et al [35] observed RMSE value of 0.92 m using OK (isotropy) geostatistical method to map the bathymetry of an Amazonian hydroelectric reservoir over Brazil; (ii) Panhalkar and Jarag [20] found the IDW method performed better (i.e., RMSE value of 7.63 m) in generating the bathymetry of Panchganga River over India; (iii) Merwade [15] observed that the OK anisotropic method achieved RMSE values in the range of 0.20 m to 0.80 m in six river reaches in the United States; and (iv) Moskalik et al [36] investigated the bathymetry and geographical regionalization using OK method and found good relationship with the observed data (i.e., r 2 value of 0.98) over Hornsund, Norway. Furthermore, we calculated the deviation for each section of interest using both IDW and OK methods.…”
Section: Comparison Of Spatial Interpolation Methodssupporting
confidence: 50%
“…In fact, both the IDW and OK methods performed quite similarly, thus one of the methods could be adopted in this study. Our result was also similar in comparison to other studies found in the literature: (i) Curtarelli et al [35] observed RMSE value of 0.92 m using OK (isotropy) geostatistical method to map the bathymetry of an Amazonian hydroelectric reservoir over Brazil; (ii) Panhalkar and Jarag [20] found the IDW method performed better (i.e., RMSE value of 7.63 m) in generating the bathymetry of Panchganga River over India; (iii) Merwade [15] observed that the OK anisotropic method achieved RMSE values in the range of 0.20 m to 0.80 m in six river reaches in the United States; and (iv) Moskalik et al [36] investigated the bathymetry and geographical regionalization using OK method and found good relationship with the observed data (i.e., r 2 value of 0.98) over Hornsund, Norway. Furthermore, we calculated the deviation for each section of interest using both IDW and OK methods.…”
Section: Comparison Of Spatial Interpolation Methodssupporting
confidence: 50%
“…Conversely, Bello-Pineda and Hernández-Stefanoni (2007) showed that the kriging method was better than IDW for mapping the bathymetry of the Yucatan submerged platform (Curtarelli et al 2015).…”
mentioning
confidence: 99%
“…To treat missing data, two common approaches are available. One is to exclude periods with missing values from data analysis, and the other is to ignore the missing data based on the tacit assumption that the data represent one continuous series [3,4]. However, these approaches may disregard useful information and bias the analysis results [2].…”
Section: Introductionmentioning
confidence: 99%